2011
DOI: 10.1042/bj20110440
|View full text |Cite
|
Sign up to set email alerts
|

Mutational analysis of allosteric activation and inhibition of glucokinase

Abstract: Glucokinase (GK) is activated by glucose binding to the substrate site, is inhibited by GK regulatory protein (GKRP) but stimulated by GK activator drugs (GKAs). To further explore the mechanisms of these processes we studied pure recombinant human GK (normal enzyme and a selection of 31 mutants) using steady state kinetics of the enzyme and tryptophan fluorescence (TF). TF studies of the normal binary GK/glucose complex corroborate recent crystallography showing that it exists in a closed conformation greatly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
41
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 28 publications
(44 citation statements)
references
References 44 publications
1
41
1
Order By: Relevance
“…A similar series of studies using the M298K mutant in the presence of an allosteric GKA treatment reported V max increase from approximately 60% to 79% of wild-type 34 . However, the restoration of V max in the presence of BAD SAHB A (S118D) occurred with modest effects on S 0.5 of this mutant, which changed from approximately 11 mM to near normal values of 8 mM (Table 2), considerably different from drastic lowering of S 0.5 to approximately 1 mM when M298K is treated with an allosteric GKA 34 . These findings reinforce the mechanistic distinction between allosteric GKAs and SAHB A (S118D) (Table 1).…”
Section: Resultsmentioning
confidence: 78%
See 3 more Smart Citations
“…A similar series of studies using the M298K mutant in the presence of an allosteric GKA treatment reported V max increase from approximately 60% to 79% of wild-type 34 . However, the restoration of V max in the presence of BAD SAHB A (S118D) occurred with modest effects on S 0.5 of this mutant, which changed from approximately 11 mM to near normal values of 8 mM (Table 2), considerably different from drastic lowering of S 0.5 to approximately 1 mM when M298K is treated with an allosteric GKA 34 . These findings reinforce the mechanistic distinction between allosteric GKAs and SAHB A (S118D) (Table 1).…”
Section: Resultsmentioning
confidence: 78%
“…Both mutations render the enzyme highly unstable 8,39,40 . Previous reports on the M298K mutation have noted substantial deficiencies in multiple enzymatic parameters 34,36,39,41 . In agreement with these reports, we observed impaired kinetic constants for this mutant, including decreased V max , diminished glucose affinity, and a decreased Hill coefficient (Fig.…”
Section: Resultsmentioning
confidence: 84%
See 2 more Smart Citations
“…GK regulatory protein) is a hepato-specific nuclear protein not found in pancreatic islet cells [8, 62]. Also highly relevant for this discussion is the fact that occupancy of the modifier region by GKA and GKRP is mutually exclusive and that glucose facilitates GKA but inhibits GKRP binding and action [4, 65, 67]. The restructuring of the allosteric modifier region and the closure of the substrate site by glucose result in a more compact, more stable enzyme as demonstrated by TF and DSC.…”
Section: Discussionmentioning
confidence: 99%